Research on the Inheritance and Development of Yatga in Inner Mongolia, China (Journal of Global Arts Studies, 2024)
Background: Inner Mongolia Autonomous Region, as the region with the highest concentration of the Mongolian ethnic population in China, has experienced relatively slow development in the inheritance and dissemination of the traditional Mongolian folk instrument yatga compared with other traditional Mongolian musical instruments. Objective: This study aims to summarize the major problems encountered in the transmission and development of the yatga in Inner Mongolia and to propose corresponding solutions. Methods: Through literature review related to the Mongolian musical instrument yatga, combined with field investigation and research, this study examines the inheritance methods, structural evolution, performance techniques, and repertoire development of the yatga in Inner Mongolia, while identifying the key issues affecting its contemporary development. Results: The research reveals that the inheritance of the yatga in Inner Mongolia currently faces several major challenges, including the backwardness of instrument-making techniques, a shortage of original instrumental compositions, and the lagging development of education and teaching related to the instrument. Conclusion: The study proposes several solutions, including the application of modern science and technology to support the inheritance of Mongolian musical instruments, innovative approaches for expanding the repertoire of Mongolian instrumental music, and the continuous promotion of Mongolian instrumental music education within schools. Furthermore, it emphasizes the importance of establishing a comprehensive social protection mechanism to provide stronger institutional support for the inheritance and sustainable development of traditional ethnic musical instruments such as the yatga.
Keywords: Inner Mongolia; ethnic musical instruments; yatga; instrument inheritance development